2009
DOI: 10.1891/0886-6708.24.6.757
|View full text |Cite
|
Sign up to set email alerts
|

Batterer Intervention Programs: A Report From the Field

Abstract: Over the past 25 years, batterer intervention has become the most probable disposition following a plea or conviction on domestic battery charges and, consequently, batterer intervention programs (BIPs) have proliferated. Despite their popularity, and recent attempts by states to regulate practice, little is known about the actual programs operating in the field. The aim of this study was to examine the philosophy, structure, leadership, curricula, and support systems of BIPs. Respondents from 276 batterer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 25 publications
(25 reference statements)
4
118
0
14
Order By: Relevance
“…Assuming that some letters were undeliverable or unopened, the response rate was probably somewhat higher. Even so, it is comparable to that of other mail surveys that involved a one-time mailing without follow-up or group incentive (Dillman et al, 2009;Price and Rosenbaum, 2009). The response rate might have been higher had we been able to send reminder letters to nonresponding groups (Asch et al, 1997).…”
Section: Methodssupporting
confidence: 58%
“…Assuming that some letters were undeliverable or unopened, the response rate was probably somewhat higher. Even so, it is comparable to that of other mail surveys that involved a one-time mailing without follow-up or group incentive (Dillman et al, 2009;Price and Rosenbaum, 2009). The response rate might have been higher had we been able to send reminder letters to nonresponding groups (Asch et al, 1997).…”
Section: Methodssupporting
confidence: 58%
“…Furthermore, perpetrators are 60% less likely to be convicted in mandatory arrest and pro-arrest states in comparison to those that have kept discretionary arrest policies (Hirschel, 2008). Also troubling is the disproportionate arrest and prosecution of men (Shernock & Russell, 2012) and the fact that men account for 83%-90% of individuals enrolled in BIPs (Cannon, Hamel, Buttell, & Ferreira, 2016;Price & Rosenbaum, 2009), a percentage that does not reflect prevalence rates of partner violence in the general population.…”
Section: Policies On Intimate Partner Violence Interventionmentioning
confidence: 99%
“…From an ecological perspective (Bronfenbrenner, 1979), this model is focused on macrolevel social factors, patriarchal cultural norms, and how they influence behavior at the family and individual levels. A web-based survey of 276 perpetrator programs in 45 different states, 53% of them indicated that they operate under a Duluth philosophy (Price & Rosenbaum, 2009). In the United States, Cannon et al (2016) reported that the Duluth model is the primary treatment approach reported by 35.6% of programs, and the secondary treatment approach reported by 11.7% of programs.…”
Section: Duluth Modelmentioning
confidence: 99%
See 2 more Smart Citations